Dry fiber placement of carbon/steel fiber hybrid preforms for multifunctional composites. (2nd January 2019) - Kühn, Florian; Rehra, Jan; May, David; Schmeer, Sebastian; Mitschang, Peter
Abstract: Integration of steel fibers (SF) in carbon fiber (CF) reinforced polymer composites (CFRPC) allows improvement of electrical conductivity while maintaining excellent mechanical properties, since SF also contribute to the load-carrying capacity. Due to their high ductility, also energy absorption and structural integrity can be improved. Within this study, a preforming process for hybrid carbon/SF preforms based on dry fiber placement (DFP) is developed and validated. The investigations cover the production of bindered SF rovings, the production of hybrid preforms via DFP of spread and nonspread SF rovings on CF noncrimp fabrics (CF-NCF) as well as the production of hybrid laminates via vacuum-assisted resin infusion (VARI). The laminate quality was evaluated by microscopic images and mechanical tensile testing. A higher SF volume content within the SF areas and more homogeneous SF layers in the preform (fewer matrix-rich zones) were achieved by processing nonspread SF rovings. The more homogeneous SF layers within the samples with nonspread SF rovings compared to spread SF rovings led to higher stiffness and strength of the specimens for tension loadings and therefore to best results. Graphical Abstract: